KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN SEBAGAI ANTESEDEN LOYALITAS PELANGGAN - Rohmat Dwi Jatmiko (Universitas muhammadiyah malang, 2012)
KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN SEBAGAIANTESEDEN LOYALITAS PELANGGANRohmat Dwi JatmikoFakultas Ekonomi dan Bisnis Universitas Muhammadiyah MalangE-mail: jetto@umm.ac.idABSTRACTThis study aims to analyze the influence of service quality on customer satisfaction and loyalty at theIslamic hospital Aisiyah Diponegoro Ponorogo (RSIADP). Data analyzed 116 unit of analysis ofquestionnaires distributed to 160 respondents from patient’s next of kin from a sample taken by quotasampling. The definition of customer in this study is the patient’s immediate family (father, mother, sonor daughter) who are waiting for patients hospitalized at least 2 consecutive days in the hospital.Structural equation modeling (SEM) with AMOS Version 5.0 procedure used to test the hypothesizedmodel showed that the quality of inpatient services significantly affect customer satisfaction andloyalty. The study found that more effective customer loyalty is built through quality of service thanthrough customer satisfaction.Keywords: quality of service, customer satisfaction, customer loyalty